IMPACT OF THE COVID-19 PANDEMIC ON QUALITY OF LIFE OF HEALTH CARE WORKERS IN PAKISTAN - Noor-ul-Huda; Arshad, Saamia; Lodhi, Fahad Saqib; Rabbani, Unaib; Anis, Salwa; Minhaj-bin-Misbah (Journal of Ayub Medical College Abbottabad, 2021)
Background: Health care workers (HCWs) working on frontlines in covid-19 pandemic are highly vulnerable to deteriorating physical and mental health. The quality of life of health care workers plays an important role in their skilful delivery of work. Our study assesses their quality of life (QOL) during covid-19 pandemic so that appropriate measures can be taken to improve their well-being. Methods: This was an online cross-sectional survey among healthcare workers of COVID-19 designated government hospitals in districts Abbottabad, Manshera and Haripur, Khyber Pakhtunkhwa, Pakistan from 23rdJune till 25thJuly, 2020. QOL was assessed using validated WHO QOL BREF. Univariate and multivariate linear regression were used to assess the factors associated with QOL among HCWs. Results: A total of 362 HCWs participated in the study. The mean scores of physical, psychological, social relationships, environmental domains were 60.7 (±17.40), 59.70 (±17.30), 67.90 (±17.90), and 58.20 (±18.40) respectively. Hospital where the respondents were working was the consistent predictor of QOL scores in all four domains with generally lower scores associated with other hospitals compared to Ayub medical hospital. Years of experience were positively associated with psychological, social relationship and environmental domains. Designation was associated with social relationship domain only. The scores were lower for trainee medical officers (adjusted Î² -11.5) and higher for house officer (adjusted Î² 10.0) and nurses and technicians (adjusted Î² 7.0) compared to heads of departments and specialists. Conclusions: Quality of life of health care workers has been affected negatively in hospitals of Abbottabad, Pakistan during COVID-19. This calls for hospital administrations, policymakers and the government to take necessary actions to protect the wellbeing of the backbone of the healthcare system.